Psycho-emotional and psychosomatic status test rates in boxing - Guzich, M. E.; Grekhova, I. P. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to obtain psychosomatic status test rates under stresses typical for modern boxing sport. Subject to the study were 30 boxers split up into Experimental Group 1 (EG1, n=15) of those qualifying for the seasonal ranking competitions; and Experimental Group 2 (EG2, n=15) composed of the boxers who failed to qualify for the seasonal ranking events. The study was designed to match both groups by the stress tolerance and psychosomatic performance rates, with the Holmes-Rahe Stress and Social Readjustment Rating Scale and the Giessen Complaint Questionnaire applied for the study purposes. The study found both of the groups, irrespective of their actual involvement in the competitive process, being exposed to the external uncertainty related stressors and facing the associating somatic problems. The boxers qualified for the top-ranking competitions, however, were tested to be more exposed to the stressors compensated by the relevant autonomic system disorders and associated with a variety of stress-coping problems.